LGBT's Position in the Laws of the Republic of Indonesia In terms of the Pancasila Perspective (Law Research Review Quarterly, 2016)
One of the phenomena that occur in the midst of the life of this nation is the rise of LGBT cases which are troubling Indonesian people. Regulations in the Criminal Code are no longer able to cover and answer existing problems. The law is substantially unable to provide a solution, due to the swift influence of globalization which is so infectious to the morals of the nation's children. In the concept of ideology explains the existence of values ​​that must be maintained, so that in the settlement that prioritizes the revitalization of a country's ideology and there is an effort to improve the ideology values ​​of the State of Indonesia to the actual ideology of the rule of law, so that the actual ideological function is no longer made as a matter. usual by every organization that exists and that is contrary to ideology in Indonesia. By using a normative legal research approach, this research wants to explain how the actual weaknesses of the LGBT problem solving process are present and explain how the concept of revitalization can solve these problems.